Kajian Desain Selubung Bangunan Apartemen RSUD Wates terhadap Radiasi Matahari - Afrizal, Zahmi (Universitas Medan Area, 2025)
The building envelope plays a very important role in determining occupant comfort and building energy efficiency. One factor that needs to be considered in building envelope design is the influence of solar radiation. Solar radiation entering a building can affect indoor temperature, lighting quality, and energy consumption for cooling and heating. Therefore, proper building envelope design can minimize the negative impacts of solar radiation, such as excessive heating and increase indoor thermal comfort. This study aims to analyze various building envelope design strategies that can reduce the impact of solar radiation. Various influencing factors such as building orientation, materials, facade surface color, shading systems, and use of glass will be discussed in this study. Through a quantitative research approach, this study aims to provide recommendations for building envelope design that not only consider aesthetic and functional aspects, but also energy efficiency and occupant comfort. Proper envelope design can reduce the need for artificial energy for lighting and cooling, and contribute to reducing carbon emissions to improve the overall sustainability of the building.